Euphemisms As A Face-Saving Strategy In A Political Leader’s Speech: A Case Study Of Barack Obama’s 2016 State Of The Union Address - Jabborova Aziza Jobirovna (International Journal Of Literature And Languages, 2025)
This study investigates the use of euphemisms as a face-saving strategy in political discourse, focusing on Barack Obama’s 2016 State of the Union Address. By analyzing the official transcript, the research identifies lexical-semantic, pragmatic, and discourse-level euphemistic strategies employed to soften sensitive topics, distribute responsibility, and maintain the speaker’s credibility. The findings reveal that lexical substitutions, agent avoidance, optimistic framing, and rhetorical devices such as repetition and parallelism are systematically used to mitigate face-threatening content. The study highlights the role of euphemisms in enhancing persuasion, managing public perception, and preserving political authority, demonstrating that strategic language choices are essential in high-stakes political communication.